Relevansi Hadits tentang Kewajiban Menuntut Ilmu dalam Menjawab Tantangan Pendidikan Modern - Suyudi; Nimas Wening Kurniannur (Tarbiyah bil Qalam : Jurnal Pendidikan Agama dan Sains, 2026)
Modern education faces major challenges in the form of globalization, technological developments, moral crises, and the secularization of the education system. In this context, the hadith of the Prophet Muhammad SAW regarding the obligation to seek knowledge remains a fundamental principle that is still relevant today. This study aims to examine the relevance of the hadith on the obligation to seek knowledge in the context of modern educational challenges marked by technological advances, moral crises, and the secularization of values. Using a library research method based on a qualitative approach, this study examines hadith texts and classical and contemporary Islamic literature. The results of the study show that the hadith of the Prophet Muhammad SAW on the obligation to seek knowledge has a universal meaning that is capable of responding to the challenges of modern education. Values such as sincerity, intellectual responsibility, and the integration of religious and general knowledge are the main principles that need to be revived amid the rapid flow of digitalization and pragmatism in modern education. The relevance of these hadiths is reflected in the need for the integration of religious and scientific knowledge, the formation of noble character, and the mastery of technology in the digital age. Thus, the hadiths on the obligation to seek knowledge provide a conceptual and practical solution to the challenges of modern education